The Silting-Up Prevention in the Geothermal Absorbent Openings of Geothermal Energy Plant Pyrzyce - Noga Bogdan; Marjanowski Jan; Biernat Henryk; Kulik Stanisław; Zieliński Bogusław; Nalikowski Arkadiusz (Chemical and Process Engineering)
The paper presents precipitation results from cold thermal water deposits that are the main cause of clogging in absorbent geothermal wells and borehole areas. As a result of physical and chemical analysis, laboratory tests and observation of the operation of a geothermal installation, a new method was developed to prevent the precipitation of sludge from cooled thermal water. The method being a modification of soft acidising was tentatively named as a super soft acidising method